Comparative proteomic analyses reveal the proteome response to short-term drought in Italian ryegrass (Lolium multiflorum). - Ling Pan; Zhongfu Yang; Jianping Wang; Pengxi Wang; Xiao Ma; Meiliang Zhou; Ji Li; Nie Gang; Guangyan Feng; Junming Zhao; Xinquan Zhang (PLoS ONE)
Drought is a major abiotic stress that impairs growth and productivity of Italian ryegrass. Comparative analysis of drought responsive proteins will provide insight into molecular mechanism in Lolium multiflorum drought tolerance. Using the iTRAQ-based approach, proteomic changes in tolerant and susceptible lines were examined in response to drought condition. A total of 950 differentially accumulated proteins was found to be involved in carbohydrate metabolism, amino acid metabolism, biosynthesis of secondary metabolites, and signal transduction pathway, such as β-D-xylosidase, β-D-glucan glucohydrolase, glycerate dehydrogenase, Cobalamin-independent methionine synthase, glutamine synthetase 1a, Farnesyl pyrophosphate synthase, diacylglycerol, and inositol 1, 4, 5-trisphosphate, which might contributed to enhance drought tolerance or adaption in Lolium multiflorum. Interestingly, the two specific metabolic pathways, arachidonic acid and inositol phosphate metabolism including differentially accumulated proteins, were observed only in the tolerant lines. Cysteine protease cathepsin B, Cysteine proteinase, lipid transfer protein and Aquaporin were observed as drought-regulated proteins participating in hydrolysis and transmembrane transport. The activities of phospholipid hydroperoxide glutathione peroxidase, peroxiredoxin, dehydroascorbate reductase, peroxisomal ascorbate peroxidase and monodehydroascorbate reductase associated with alleviating the accumulation of reactive oxygen species in stress inducing environments. Our results showed that drought-responsive proteins were closely related to metabolic processes including signal transduction, antioxidant defenses, hydrolysis, and transmembrane transport.